Review article: anti‐adhesion therapies for inflammatory bowel disease. Issue 6 (30th January 2014) - Lobatón, T.; Vermeire, S.; Van, G.; Rutgeerts, P.
Summary Background A high proportion of patients with inflammatory bowel disease (IBD) do not achieve clinical remission with the current therapies including mesalazine (mesalamine), immunossupresants (IMS) and antibodies against tumour necrosis factor (anti‐TNF). Moreover, IMS and anti‐TNF involve a nonnegligible risk for infections and/or malignancies. The anti‐adhesion molecules are one of the most interesting new treatments because of their gut‐selectivity. Aim To review the physiopathology of the adhesion molecules and the current drugs targeting this mechanism. Methods We performed a literature review in PubMed and in clinicaltrials.gov using the terms 'anti‐adhesion molecules', 'inflammatory bowel disease', 'natalizumab', 'vedolizumab', 'AMG181', 'Etrolizumab', 'PF‐00547659', 'AJM300', 'Alicaforsen' and 'CCX282‐B' up to November 2013. Results A total of eight drugs were found including those targeting the α4β1, α4β7 or αEβ7 integrins as well as the ICAM‐1 and MAdCAM‐1 addressins and the chemokine receptor 9. The rationale for these drugs is the blockade of gut‐homing T lymphocytes and the ones targeting the α4β7/MAdCAM‐1 interaction presented the most promising results in luminal disease. Vedolizumab, an α4β7 antibody, has completed phase 3 trials with very positive results especially for ulcerative colitis. However, many questions remain unanswered such as the effect of these therapies in perianal disease and extraintestinal manifestations. Conclusions The blockade of the α4β7/MAdCAM‐1 interaction and especially vedolizumab is an effective and safe gut‐specific treatment for IBD. Further studies are needed to clarify the efficacy and safety of the other anti‐adhesion drugs and to define the specific indications of these therapies in the different scenarios of IBD.